2023
DOI: 10.3390/nu15081970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lacticaseibacillus paracasei N1115 on Immunomodulatory and Gut Microbial Composition in Young Children: A Randomized, Placebo-Controlled Study

Abstract: Lactobacillus paracasei N1115 (Lp N1115) was isolated from fermented milk products. The administration of Lp N1115 is safe and well tolerated in Chinese children, but its effectiveness among young Chinese children is still unclear. To investigate the efficacy of Lp N1115 as a probiotic to enhance gut development in Chinese infants and toddlers born by cesarean section, 109 healthy and cesarean-delivered infants aged 6–24 months were recruited for a 12-week randomized, placebo-controlled trial, with 101 finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A randomised controlled trial of 101 infants born via CS in China assessed the effectiveness of the Lactobacillus paracasei N1115 strain in improving gut development, showing that this strain increased the Lactobacillus content and the sIgA levels in the stools while reducing salivary cortisol levels in both infants and children. The latter was more pronounced in infants aged 6–12 months [ 147 ]. In a placebo-controlled, double-blind, randomised trial involving 110 healthy full-term infants, it was demonstrated that supplementation with Bifidobacterium longum subsp.…”
Section: Role Of Infant Gut Microbiota In the Immune Responsementioning
confidence: 99%
“…A randomised controlled trial of 101 infants born via CS in China assessed the effectiveness of the Lactobacillus paracasei N1115 strain in improving gut development, showing that this strain increased the Lactobacillus content and the sIgA levels in the stools while reducing salivary cortisol levels in both infants and children. The latter was more pronounced in infants aged 6–12 months [ 147 ]. In a placebo-controlled, double-blind, randomised trial involving 110 healthy full-term infants, it was demonstrated that supplementation with Bifidobacterium longum subsp.…”
Section: Role Of Infant Gut Microbiota In the Immune Responsementioning
confidence: 99%
“…The study by Li et al [90] investigated the efficacy of Lactobacillus paracasei N1115 (Lp N1115) as a probiotic in improving gut microbial composition and immunomodulation among Chinese infants and children born through CS.…”
Section: Quality Assessment and Risk Of Biasmentioning
confidence: 99%